Social participation and human development in three protected areas of Costa Rica. - Marín-Cabrera, Melissa (2022)
[Introduction]: Wildlife protected areas are an ideal source of information to analyze the characteristics of social participation in environmental issues because they are spaces where conservation and human development interests coexist. [Objective]: This document analyzes the functional dimension of the social participation in high biodiversity areas, understood as the ability to transform environmental values into development opportunities. [Methodology]: It focuses on three wildlife protected areas as places where nature and humans interact through the use of ecosystem services provided by protected areas. This generate alliances but also socio-environmental conflicts that are key in the sustainability of protected areas. The characteristics and influences of organizational participatory networks in three wildlife protected areas of Costa Rica were analyzed through Social Network Analysis and the Human Development approach. [Results]: The results show that, although the functionality of social networks is independent of the restrictions or ease of use of natural resources, it is closely linked to the existence of multisectoral dialogue platforms. The absence of these spaces creates highly centralized networks that are profoundly dependent on the priorities of a few sectors that are generally the most influential. Participation networks with these characteristics are considered pseudo-satisfiers of universal human needs. [Conclusions]: Environmental education and conservation actions are positioned as promoters of participation because, in practice, they link conservation and development. Although these are considered synergistic satisfiers, the high centrality of the networks can limit their scope.